Round Trip to Hell in a Flying Saucer: The Relationship between Conventional Christian and Paranormal Beliefs in the United States - Mencken, F. Carson (Sociology of religion, 2009)
In this paper we examine the relationship between conventional Christian and paranormal beliefs. Conventional Christian beliefs are those such as belief in Heaven, Hell, and the existence of God. Paranormal beliefs include belief in UFOs, astrology, haunting, communication with the dead, and Bigfoot. We test three hypotheses (deviance) (marginalization, small step, and compatibility) about the relationship between these two belief types with factor analysis and regression analysis. The data we use are from the Baylor Religion Survey, a national random sample collected by the Gallup Organization in fall 2005. The factor analysis results show that there are two well-defined spheres of supernatural beliefs, one conventional Christian and one paranormal. We find a net positive relationship between these two belief clusters. However, a test of the compatibility hypothesis shows that church attendance and religious tradition moderate the effects of conventional Christian beliefs on paranormal beliefs. We conclude with a discussion of the implications for theory and research.